THE BASIC OF EMPLOYEE TRAINING AND DEVELOPMENT AND TRAINING METHODS TO INCREASE EMPLOYEE PRODUCTION - R. Jayam; A. Gayathri (International Journal of Psychosocial Rehabilitation, 2020)
-All organizations must control the major four resources: people, information, equipment and money. Investments in better tools and instruments may increase production or decrease waste. Information is strength; information about customers, products and prices are important to every business. Investments in training and development of employee can increase more productive or more efficient in their jobs, directly contributing to the outcome. Dale S. Beach defines training as ‘the organized procedure by which people learn knowledge and/or skill for a definite purpose’. Training refers to the teaching and learning activities carried on for the primary purpose of helping members of an organization acquire and apply the knowledge, skills, abilities, and attitudes neededbyajobandorganization.